Number 1
Show
that if n is positive integer
P(n) : 1+2+………..+
n = [n (n+1)]/2
Basis
step : let n = 1
1 = [1(1+1)]/2
1 = 1
(PROVE)!!!
Inductive
step : let n=k; k= k+1
1 + 2 +…+ n = [n
(n+1)]/2
1 + 2
+…+ k= [k (k+1)]/2
1 + 2 +…+ k + (k+1) = (k+1) [(k+1)+1]/2
[k(k+1)]/2 + (k+1) = [(k+1) (k+2)]/2
[k(k+1) +2k+2]/2
= [(k+1) (k+2)]/2
[k 2 + k + 2k +2]/2 = [k2 +
2k + k+ 2]/2
Number 2
Basis Step
if P(n) is true then can continue to the next step.
Inductive Step
If P then Q
P is the hyphothesis while Q is conclusion
Thus,
If P(n) is true, Then P(n+1) is true/false
Number 3
#Formulas:
Show
that if n is a positive
integer, then
1
+ 2+…..+n
=
Solution:
Let P(n) be
the proposition that the sum of the first n
positive integers, 1+2+…+n=n(n+1)/2. We must do
two things to prove that P(n) is
true for n = 1,
2, 3,
. . .
Namely,
we must show that P(1)
is true and that the conditional statement P(k)
implies P(k +
1) is
true for k = 1,
2, 3,…..
BASIS
STEP: P(1)
is true, because 1 =
(The
left-hand side of this equation is 1 because
1 is the sum of the first positive integer. The right-hand side is
found by substituting 1 for n
in n(n +
1)/2.)
INDUCTIVE
STEP: For the inductive
hypothesis we assume that P(k) holds
for an arbitrary positive integer k.
That is, we assume that
1
+ 2+· ·
·+k =
Under
this assumption, it must be shown that P(k +
1) is
true, namely, that
1
+ 2+· ·
·+k + (k
+ 1) ==
is
also true. When we add k + 1
to both sides of the equation in P(k),
we obtain
1+2+....+k+(k
+ 1)=+(k+1)
=
=
This
last equation shows that P(k +
1) is
true under the assumption that P(k) is
true. This completes the inductive step.
We
have completed the basis step and the inductive step, so by
mathematical induction we know that P(n) is
true for all positive integers n.
That is, we have proven that 1 + 2+·
· ·+n =n(n
+ 1)/2
for all positive integers n.
#Divisibility
properties
Proposition:
For any integer n≥1, 7n
- 2n is divisible
by 5. (P(n))
Proof
:
1)
Basis step:
The
statement is true for n=1: (P(1))
71
– 21 =
7 - 2 = 5 is divisible by 5.
2)
Inductive step:
Assume
the statement is true for some k≥1 (P(k))
(inductive
hypothesis) ;
We
are given that
P(k):
7k - 2k
is divisible by 5.
(1)
Then
7k
- 2k = 5a for
some aÎZ .
(2)
We
need to show:
P(k+1):7k+1
- 2k+1 is
divisible by 5.
(3)
7k+1
- 2k+1 = 7·7k
- 2·2k = 5·7k
+ 2·7k - 2·2k
=
5·7k + 2·(7k
- 2k) = 5·7k
+ 2·5a (by (2))
=
5·(7k + 2a) which
is divisible by 5.
Show
that it is true for k+1.
(P(k+1))
Thus,
P(n) is true by induction.
#Inequalities
Theorem:
For all integers n≥5, n2 < 2n.
(P(n))
Proof
(by induction):
1)
Basis step:
The
statement is true for n=5: (P(5))
52 =25 < 32 = 25.
2)Inductive
step:
Assume
the statement is true for some k≥5 ; (P(k))
We
are given that
P(k):
k2 < 2k.
(1)
We
need to show:
P(k+1):
(k+1)2 < 2k+1.
(2)
(k+1)2 = k2+2k+1 < k2 +2k
(since k≥5)
< 2k + 2k (based
on (1))
= 2·2k = 2k+1.
Show
that it is true for k+1 . (P(k+1))
Thus,
P(n) is true by induction.